Agromeliorative Efficiency of Phosphogypsum Application on Irrigation Saline Soils in the Northern Steppe of Ukraine - Makarova, Tetiana; Макарова, Тетяна Костянтинівна; Domaratskiy, Ye.; Домарацкий, Є.; Hapich, Hennadii; Гапіч, Геннадій Васильович; Kozlova, O.; Козлова, О. (My University, 2021)
The present research represents the influence of chemical reclamation on the saline regime of the soil. Irrigation with limited water suitable for irrigation increased exchangeable sodium in the soil exchange complex to 5% and in the aqueous soil extract by 30%. Phosphogypsum was used as a chemical ameliorant in stock for three years under irrigation conditions and without it. It was applied at rates of 1.4, 3 (in spring) and 6 (in autumn) t/ha. The application of ameliorant in the spring a t the rates of 1.4 and 3 t ha−1 under irrigation caused to reducing the ratio of Na/Ca on average from 3 years to 2.53 and 1.51. It was sulfate type of salinity for all period of the time. Sodium exchange was decreased by application rates of phosphogypsum to 2.3% total amount of the exchangeable cations without irrigation (application of ameliorant in autumn) as compared to the control variant. Sodium exchange was decreased to 3.7% with a total amount of the exchangeable cations with irrigation (application of ameliorant in spring). In the first year after the second application of phosphogypsum there were the lowest rates of the density had the variants without irrigation. The density in this period was 1.17–1.2 g cm−3, that was less on 0.04–0.96 g cm−3 as compared with the results the first year after first application. Це дослідження представляє вплив хімічної меліорації на засолений режим грунту. Зрошення обмеженою кількістю води, придатної для зрошення, збільшувало обмінний натрій в грунтово-обмінному комплексі до 5% і в водному грунтовому екстракті на 30%. Фосфогіпс використовувався як хімічна мелиоранта протягом трьох років в умовах зрошення і без нього. Вносили з розрахунку 1,4, 3 (навесні) і 6 (восени) т / га. Застосування меліорантів навесні за ставками 1,4 і 3 т га -1прі зрошенні призвело до зниження співвідношення Na / Ca в середньому з 3 років до 2,53 і 1,51. Солоність була сульфатної на всі часи. Обмін натрію був знижений дозами внесення фосфогіпсу до 2,3% від загальної кількості обмінних катіонів без зрошення (внесення мелиоранта восени) в порівнянні з контрольним варіантом. Обмін натрію був знижений до 3,7% з загальною кількістю обмінних катіонів при зрошенні (внесення мелиоранта навесні). У перший рік після другого внесення фосфогіпсу найнижчі показники густоти були у варіантів без поливу. Щільність в цей період становила 1,17-1,2 г см -3, що на 0,04-0,96 г см -3 менше. в порівнянні з результатами першого року після першого застосування.
Агромеліоративних ефективність застосування фосфогіпсу на зрошуваних засолених грунтах північному степу України
Keywords: saline composition of soil; сольовий склад ґрунту; chemical reclamation; хімічна меліорація; irrigation; зрошення; phosphogypsum; фосфогіпс